(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Seventy two sugarcane fields in the sugarcane plantation of Kenana SugarCompany, Sudan, were inspected during 2003/2004 and 2004/2005 seasons to study theextent of infestation by the white grubs in relation to cane crop cycles and variety. Fivestandard pits were made in different locations across each field, and the insects in eachpit were counted. The results showed that in all crop cycles sugarcane was infested bythe grubs with variable levels. Significantly lower infestation was recorded from theplant cane than the second or the fourth ratoon which were equally infested. The twomain sugarcane varieties, Co6806 and Co997, were comparably infested by the grubs.The trend of infestation during the two seasons was not different.